1797
DOI: 10.5962/bhl.title.727
|View full text |Cite
|
Sign up to set email alerts
|

Caroli a Linné Species plantarum :exhibentes plantas rite cognitas, ad genera relatas, cum differentiis specificis, nominibus trivialibus, synonymis selectis, locis natalibus, secundum systema sexuale digestas.

Abstract: An hiltorical Accout of two fpecies of Lycoper-. don. b) C, Bryant. Lond. in 8-Cavan, ilijf^M onadelphiae cla/ns diiTcrtatlones decem Auctorê . Ant, Jof, Cavaiiilles. iVIatnti 1790. in 4 Lavan. icon, Ejusdcni lcun^s ct defcriptiones plantarum qTiire aut fpuiite m Hifpania crefcunt auc in hortis hofpitantnr. Vol. I -III. Matriti in Fol» Collectauea Societ. re^, Havnienf. Vol I II niae 1773. 1775.^in Q. tomm&nt. goett, Novi Comment. Soc, reg. goett, Tom I Goeiting. 1771 -1780 iu 4 Cothen, dijpof. Ch And. Cotheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Only a small number of authors of the 19th century applied the name S. aucuparia in the narrow sense according to Haller's diagnosis (e.g., Schultes, 1814), whereas most observed that the underside of the leaves is more commonly hairy in this species (e.g., Willdenow, 1799;Hedlund, 1901), and the hairy morphotype has become considered typical of the species since then. The lectotype selected here is an element upon which the species diagnosis in Linnaeus (1753) was based (Art.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of authors of the 19th century applied the name S. aucuparia in the narrow sense according to Haller's diagnosis (e.g., Schultes, 1814), whereas most observed that the underside of the leaves is more commonly hairy in this species (e.g., Willdenow, 1799;Hedlund, 1901), and the hairy morphotype has become considered typical of the species since then. The lectotype selected here is an element upon which the species diagnosis in Linnaeus (1753) was based (Art.…”
Section: Discussionmentioning
confidence: 99%
“…This separation has since been followed by most authors who have considered both taxa, either as different species of one same genus [Exacum (Willdenow, 1798;Lamarck & Candolle, 1805), Cicendiola (Bubani, 1897), Microcala (Don, 1837(Don, -1838, Cicendia (Grisebach, 1838;Nyman, 1878Nyman, -1882Willkomm, 1870)], or as belonging to different genera [Exacum and Chironia L. (Willdenow, 1798), Microcala and Exacum (Hoffmannsegg & Link, 1813-1820, Microcala and Cicencia (Grisebach, 1845;Bentham & Hooker, 1876;Gilg, 1895), Cicendia andExaculum (Caruel, 1884-1886;Quézel & Santa, 1963;Tutin, 1972;Guinochet & Vilmorin, 1975;Pignatti, 1982;Franco, 1984;Greuter & al., 1986;Gamissans & Jeanmonod, 1993;Thiv & Kadereit, 2002;Ouyahya, 2007;Díaz Lifante, 2012)].…”
Section: Typification Of Gentiana Pusillamentioning
confidence: 99%
“…He called Elettari of Rheede Amomum repens Sonn. (Sonnerat, 1782: 272), and called "Cardamomum minus" of Rumphius Amomum cardamomum (Willdenow, 1797). By so doing, he had gone against Linnaeus's intention to call the Malabar cardamom Amomum cardamomum (Maton, 1811;Burkill, 1930;Burtt & Smith, 1972a).…”
Section: From Solander's Mss Translationmentioning
confidence: 99%